RURAL INFRASTRUCTURE STRATEGY FOR POVERTY REDUCTION IN NIGERIA: YOBE IFAD-CBARDP EXPERIENCE - Galadima, M. (European Scientific Journal, ESJ, 2014)
Rural development is a veritable tool for fighting poverty and achieving economic prosperity at the grassroots level. The concept of rural development embraced by most countries connotes a process through which rural poverty is alleviated by sustained increases in the productivity and incomes of low – income workers and households. The major thrust of this study was to assess the rural infrastructure strategy for poverty reduction implemented by IFAD Community-Based Agricultural and Rural Development Programmme in Yobe State, Nigeria. Objectives were achieved using multi-stage sampling techniques. A well-structured questionnaire was used to elicit primary data from respondents. Secondary data was the base line data of IFAD-CBARDP. Descriptive statistical tools were utilized for analyses and the respondents’ level of satisfaction with the infrastructure provided was obtained using likert scale. The findings revealed that, majority (51%) of respondents were male with age ranging between 20 and 65 years averaging 40 years. About 97% were married having a household size range of 5-10 persons and about 68% had formal education. The result for the provision of basic infrastructure by IFAD-CBARDP based on respondents’ benefit indicates that water had the highest accessible basic infrastructure by respondents with 91% whereas, Schools provision was recorded as 2nd benefitted infrastructure, Health centres 3rd infrastructure with 64%. Respondents also highlighted their benefit on Para vet clinic, Culvert, Vocational centres, Latrine and staff quarters 16%, 13%, 7%, 3% and 2% respectively. Respondents’ level of satisfaction on the infrastructure provided was perceptibly satisfactory. Therefore, it was recommended that, IFAD-CBARDP should be replicated in other States of the Federation in order to record a national poverty improvement. Hence, programme planners and implementers are urged to intensify awareness creation among rural dwellers and adopt the use of community driven development approach (CDD) in the execution of rural development projects with poverty alleviation thrust as in the case of IFAD-CBARDP.